Students’ engagement: empirical investigation into technology acceptance and pre-class activities - Chai, Tan Choe; Farid, Nur Faridah Shaik; Haur, Jason Lee Song; Mahmud, Malissa Maria; Yaacob, Yazilmiwati; Zakaria, Noor Syamilah; Saparman, Md Sairolazmi; Mustamam, Nur Izzati; Ishak, Noor Syamimi (Institute of Advanced Engineering and Science, 2024)
The COVID-19 pandemic has led to a significant transformation in the field of education, with a notable shift towards online learning worldwide including higher education institutions. However, one of the major concerns faced by educators is ensuring students’ active participation and engagement in the online learning environment. In maintaining the quality of education and achieve desired learning outcomes, it is crucial to understand the factors that influence students’ engagement. The main objective of this study is to investigate the impact of technology acceptance and pre-class activities on the engagement levels of higher education students in online learning platforms. To conduct the research, a cross-sectional approach was employed, and data was collected from 1,692 students at Sunway College and Sunway University through a Google survey form administered between January and March 2022. The findings of this study reveal a positive and significant correlation between students’ acceptance of technology and their level of engagement in the online learning process. Moreover, the study highlights the empirical significance of pre-class activities in fostering student engagement in online classes. These research findings provide valuable insights for educational institutions, practitioners, and policymakers, enabling them to enhance the effectiveness of online learning initiatives.